1999
DOI: 10.1097/00004872-199917121-00003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dental pain perception and 24 hour ambulatory blood pressure

Abstract: The correlation between both baseline and 24 h blood pressure and pain perception has been confirmed in a large group study of normotensive and hypertensive subjects. Moreover, even among the hypertensive range of blood pressure, the higher the blood pressure is, the lower the sensitivity to pain is. These findings strengthen the hypothesis of a role of the degree of blood pressure elevation in modulating pain sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
0
15
0
4
Order By: Relevance
“…Subjects with higher, but still normotensive, blood pressure values reported less pain during this mechanical pain maneuver. Guasti et al (1999) demonstrated that normotensive and hypertensive subjects differed with respect to pain threshold. The relationship between pain threshold and ambulatory systolic pressure measured over a 24 h period achieved the strongest correlation (N = 181, r =0.31, PB 0.0001).…”
Section: Relationship Between Tonic Blood Pressure Le6el and Pain Senmentioning
confidence: 99%
“…Subjects with higher, but still normotensive, blood pressure values reported less pain during this mechanical pain maneuver. Guasti et al (1999) demonstrated that normotensive and hypertensive subjects differed with respect to pain threshold. The relationship between pain threshold and ambulatory systolic pressure measured over a 24 h period achieved the strongest correlation (N = 181, r =0.31, PB 0.0001).…”
Section: Relationship Between Tonic Blood Pressure Le6el and Pain Senmentioning
confidence: 99%
“…These individuals with low pain sensitivity (higher pain thresholds) may have greater HR increases during pain 36 or elevated BP at baseline. [37][38][39][40] Few investigations have addressed the correlation of pain scores and abnormal vital signs (HR, BP, and RR) in ED populations. In two unpublished studies, investigators have attempted to correlate vital signs and pain scores in ED patients.…”
Section: Resultsmentioning
confidence: 99%
“…Muitos estudos não conseguiram esclarecer esta dúvida (Good et al, 1999;Cooke et al, 2004;Vaajoki et al, 2010;Wakim et al, 2010), embora alguns autores descrevem que a dor está a associada a fatores emocionais (Bernatzky et al, 2011). Alguns autores, afirmam que a diminuição da ansiedade pré-operatória pode diminuir a percepção de dor e que a música pode influenciar na intensidade de dor nas primeiras horas pós-operatórias, o que é questionável, pois o paciente neste período ainda poderá estar sob efeito analgésico anestésico (Vaajoki et al, 2010 (Guasti et al, 1999;Bavitz, 2006). Entretanto, são necessários mais estudos para entender a correlação fisiológica entre hipertensão e dor.…”
Section: Discussionunclassified
“…Alguns autores comentam que pacientes hipertensos costumam ter menos sensibilidade ao estímulo de dor que normotensos como Bavitz (2006), Guasti et al (1999), Guasti et al (2002). Segundo Guasti et al (1999) quanto maior a elevação da pressão arterial menor a reação do indivíduo ao estímulo de dor.…”
Section: A Dor Pós-operatória E Sua Relação Com Ansiedadeunclassified
See 1 more Smart Citation